2011
DOI: 10.3989/graellsia.2011.v67.032
|View full text |Cite
|
Sign up to set email alerts
|

New distribution data on Spanish autochthonous species of freshwater fish

Abstract: Over the last two years (2008-2010) we performed a monitoring project to update the Spanish freshwater fish fauna. We have collected in 785 sampling localities homogeneously distributed throughout Spain each year. We find as the most important result of this study the occurrence of several species that constitute new records for some rivers or basins in Spain: Lampetra planeri, Petromyzon marinus, Barbus haasi, Iberochondrostoma lemmingii, Squalius alburnoides, Squalius carolitertii, Squalius malacitanus, Cobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…On average, the size of tagged nase was 143 ± 26 mm. Although the literature describes maximum lengths of 500 mm for this species [26], captured nase in the Tormes river basin do not exceed 250 mm in length. However, most of them were also sexually mature individuals.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…On average, the size of tagged nase was 143 ± 26 mm. Although the literature describes maximum lengths of 500 mm for this species [26], captured nase in the Tormes river basin do not exceed 250 mm in length. However, most of them were also sexually mature individuals.…”
Section: Resultsmentioning
confidence: 86%
“…= 1, p < 0.0001). The average size of barbel tagged downstream of the dam was 336 ± 47 mm, and all of them were sexually mature [26]. On average, the size of tagged nase was 143 ± 26 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a work by De Leeuw and Winter [53] in the lowland rivers Meuse and Rhine in the Netherlands, the authors reported more movements of the common barbel Barbus barbus and common nase Chondrostoma nasus during both summer-early fall (July-October) and spring (spawning season for both species). It is highly likely that such activity observed in the lift is related to reproductive migrations, which takes place during these periods, particularly in summer [40,41], when these potamodromous species migrate upstream to seek areas for reproduction, typically in gravel and pebble beds located in upstream tributaries [39]. These species also showed movements outside their usual spawning period, displaying a second peak in early-fall (September-October), a result that is also consistent with other studies, in which "out of season" movements may reflect a search for winter, feeding or thermal refuges, as it has been observed in other potamodromous cyprinids [15,54].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this is particularly important as potamodromous fish are key components of the lower and middle reaches of temperate rivers [38] and sensitive to river regulation and longitudinal fragmentation [16]. Within the fish community present in the study area, the cyprinids Iberian barbel Luciobarbus bocagei (Steindachner, 1864) (hereafter barbel) and Northern straight-mouth nase Pseudochondrostoma duriense (Coelho, 1985) (hereafter nase), and the salmonid brown trout Salmo trutta fario (Linnaeus, 1758) (hereafter trout) are amongst the most abundant species in northern Iberian rivers [39] and were therefore the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Perea et al (2011) reported this species for the first time from the upper reaches of the Alberche River (a tributary of the Tagus basin in central Spain) and in the Oitavén River (a tributary of the Verdugo River in northwestern Spain). Except for the populations in the Tagus basin, this species is listed as vulnerable (VU) in the Spanish Red Data Book (Doadrio 2001) and was recently upgraded as endangered (EN) , but is in contrast recorded as least concern (LC) in both the IUCN Red List of Threatened Species (Crivelli 2006) and the European Red List of Freshwater Fishes (Freyhof & Brooks 2011).…”
Section: Introductionmentioning
confidence: 99%